#### Answer

290

#### Work Step by Step

Substitute 6 for x in the equation.
9$(6)^{2}$ - 7(6) + 8
= 9(36) - 7(6) + 8
= 324 - 42 + 8
= 290

Published by
Pearson

ISBN 10:
0321785045

ISBN 13:
978-0-32178-504-6

290

Substitute 6 for x in the equation.
9$(6)^{2}$ - 7(6) + 8
= 9(36) - 7(6) + 8
= 324 - 42 + 8
= 290

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.